Association of malocclusion, happiness, and oral health–related quality of life (OHRQoL) in schoolchildren. (30th July 2015) - da Rosa, Guilherme Nascimento; Del Fabro, Joana Possamai; Tomazoni, Fernanda; Tuchtenhagen, Simone; Alves, Luana Severo; Ardenghi, Thiago Machado
Abstract: Objective: The aim of this study was to assess the impact of malocclusion on children's oral health–related quality of life (COHRQoL) and self‐reported happiness. Methods: A cross‐sectional study was conducted in a representative sample of 12‐year‐old schoolchildren from Santa Maria, South Brazil. Four calibrated examiners carried out clinical exams to evaluate malocclusion [Dental Aesthetic Index (DAI)], dental caries (DMFT), and dental trauma (O'Brien classification, used in the Children's dental health survey in the UK, 1994). Participants answered the Brazilian versions of the Child Perceptions Questionnaire (CPQ11‐14 ) and the Subjective Happiness Scale (SHS). Parents completed a structured questionnaire regarding socioeconomic status. Data analysis was conducted using multilevel Poisson regression models. Results: A total of 1, 134 adolescents (boys: 45.8 percent; girls: 54.1 percent) were enrolled in the study. The DAI overall score ranged from 13 to 63 (mean: 25.19, standard error: 0.19); 57.6 percent of the subjects had minor or no malocclusion and 24.4 percent had definite malocclusion. Severe malocclusion and handicapping malocclusion were found in 10.4 percent and 7.4 percent of the subjects, respectively. After adjustment, the severity of malocclusion was associated with high mean values of the CPQ11‐14 overall score, and the emotional well‐being and social well‐being domains were the most affected. Lower levels of happiness were also associated with the severity of malocclusion: those with definite malocclusion presented lower scores on the SHS scale (Rate Ratio 0.97; 95 percent CI 0.94‐0.99). Conclusion: Malocclusion had a negative impact on COHRQoL and happiness, mainly on the emotional and social domains.